2016
DOI: 10.1097/ijg.0000000000000309
|View full text |Cite
|
Sign up to set email alerts
|

Deep Sclerectomy With Mitomycin C and Injectable Cross-linked Hyaluronic Acid Implant: Long-term Results

Abstract: DS with Healaflow and MMC seems to be an effective and safe technique to lower IOP in patients affected by open-angle glaucoma, with few postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
0
14
1
Order By: Relevance
“…Goniopuncture was needed in 33 of 35 eyes in our study. The frequency is higher than previously reported (Shaarawy et al 2001;Ollikainen et al 2011;Bettin et al 2016). However, Anand & Pilling (2010) followed 258 patients after deep sclerectomy for a mean of 40 months.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Goniopuncture was needed in 33 of 35 eyes in our study. The frequency is higher than previously reported (Shaarawy et al 2001;Ollikainen et al 2011;Bettin et al 2016). However, Anand & Pilling (2010) followed 258 patients after deep sclerectomy for a mean of 40 months.…”
Section: Discussioncontrasting
confidence: 71%
“…; Bettin et al. ). However, Anand & Pilling () followed 258 patients after deep sclerectomy for a mean of 40 months.…”
Section: Discussionmentioning
confidence: 98%
“…Healaflow® (Aptissen S.A., Plan Les Ouates, Switzerland) is a transparent hydrogel, developed and marketed for use in glaucoma filtering surgery, where its purpose is to maintain the bleb and limit postoperative fibrosis [32][33][34]. In this application, the gel is retained for 3-6 months [33], whereas it was retained in the vitreous space for at least a few weeks when evaluated as an experimental vitreous substitute [26].…”
Section: Vitreous Substitutesmentioning
confidence: 99%
“…[ 24 25 ] Recent studies suggested that the injection of cross-linked sodium hyaluronate gel under scleral flap and conjunctiva could inhibit the process of local fibrosis and vascularization and reduce the possibility of bleb failure, maintaining an effective filtration, and improving the long-term success rate of penetrating and nonpenetrating glaucoma surgeries. [ 15 20 26 27 ] In this prospective study, we compared the safety and efficiency of trabeculectomy with cross-linked sodium hyaluronate gel injection for Chinese glaucoma patients and followed up for 5 years. Our data indicated that both trabeculectomy alone and trabeculectomy with cross-linked sodium hyaluronate gel injection group witnessed efficient lowering of IOP, while the patients in the cross-linked sodium hyaluronate gel injection group achieved more IOP reduction at 1, 3, and 5 years after operation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 14 15 16 ] Other studies have also suggested that intraoperative implantation of sodium hyaluronate gel may prevent bleb scarring, fibrosis, adhesion and improve IOP. [ 17 18 19 20 ] However, limited randomized and case-controlled studies have been conducted to investigate the long-term outcomes of cross-linked sodium hyaluronate gel applied in trabeculectomy in patients with glaucoma.…”
Section: Introductionmentioning
confidence: 99%